Risk of contamination of beef carcasses with Escherichia coli O157:H7 from slaughterhouses in Nairobi, Kenya - Mwai, C.W. (University of Nairobi, 2011)
The study was carried out in three abattoirs supplying meat to butcheries in Nairobi, and its environs. The objectives of the study were to assess the level of contamination of carcasses with E. coli O157:H7 in the slaughterhouses, determine the critical control points and train the slaughterhouse managers on practices to reduce carcass contamination. Three slaughterhouses with different level of hygiene control, classified as export, local improved and typical local, were selected. Three hundred cattle were tracked along the slaughtering process to sample faeces and carcass. A rectal faecal sample f was taken from each animal after stunning. Two carcass sites, flank and brisket were swabbed after flaying, evisceration and washing. In total seven samples were taken from each carcass. E. coli O157 was isolated by culture and serotyped using card agglutination test. The isolates were further tested for verotoxin production. Monte Carlo simulation was run to determine the risk of carcass contamination. A HACCP model was developed for one of the abattoirs. Interviews were done with slaughter house workers to test their knowledge, attitudes and practices towards slaughtering hygiene. Identified gaps on hygiene from slaughter personnel questionnaire were used to develop training materials for slaughterhouse managers and staff. E. coli O157 was detected from the faecal and carcasses samples at different stages of carcass dressing. Two hundred and eighty (280) out of 2,100 samples (13.3%) were IMViC (++--) positive for E. coli. Sorbitol MacConkey negative isolates were presumptive E. coli O157. After serotyping with O157, 92 out of 280 (4.3%) isolates, were positive for E. coli O157. Forty-two isolates of the 92 were tested for verotoxin production, eight were positive for VT1 only while two were positive for both VT1 and VT2. The risk of a carcass being contaminated with E. coli O157 in the abattoir was 29, 38 and 48 carcasses per 1000 slaughtered animals for the export, the typical local and the local improved abattoirs respectively at 90% confidence interval. There were significant differences in prior training received by the workers in the typical local abattoir and the local improved (p=0.001) but there was no significant difference between the export and the typical local slaughterhouse and between the export and the local improved slaughterhouse. There was a significant difference (p=0.025) noted in the hand washing practice between the local improved and the typical local slaughterhouse. Number of workers playing more than one role in the slaughter process was also significant (p= 0.027) between the typical local and the local improved slaughterhouse. These factors may have contributed in the differences in carcass contamination in the three slaughterhouses. Slaughterhouse owners and staff were trained on good hygienic practices, food borne illnesses and risk of contamination of carcasses. Evaluation done one month after the training showed there was no change in the hygiene practices of the workers. This may have been contributed by lack of facilities like hot water, soap and disinfectants in typical and local improved slaughterhouses. Lack of motivation by the management and paying of the workers depending on the kill may affect the hygiene levels and workers attitude towards hygiene. This study shows that there is a risk of carcass contamination with E. coli O157 in all the different categories of slaughterhouses. Workers and operations hygiene are important factors contributing to this risk.